Model of Destination Image, Tourist Motivation, Satisfaction, and Revisit Intention in Wendit Waterpark, Malang Regency - Wirawati, Dayang Kalih Shafira; Wijayanti, Wawargita Permata; Dinanti, Dian; Suryani, Tia Adelia; Rapudin, Armei; Shafira, Salmaa (Journal of Regional and Rural Studies, 2024)
Wendit Waterpark is one of the famous tourist destinations in Malang Greater Area. This research aims to analyze the condition of image destination, tourist motivation, satisfaction, and revisit intention to Wendit Waterpark and examine the relation among those four variables using Structural Equation Model (SEM). Data collection was conducted by using questionnaire with 100 respondents. We applied a descriptive quantitative to identify condition of image destination, tourist’s motivation and satisfaction, and their revisit intention to Wendit. Result shows that there is a significant and strong relation among image destination, motivation, satisfaction, and revisit intention. It means that it is needed some improvements to enhance the condition of image destination of Wendit Waterpark, then it will improve motivation and satisfaction, and also revisit intention to this tourism destination.